Pendidikan Karakter Berbasis Pancasila: Paparan Sejarah Ideologi, Ideologi Pancasila dan Relevansinya di Era Digital - Hardiyanti Hardiyanti (SASDAYA: Gadjah Mada Journal of Humanities, 2021)
This article aims to give a brief explanation in the importance of incorporating Pancasila in the education in Indonesia. Pancasila as the state ideology becomes the unifying force of inspiration for the nation, which in this case strictly means ethnic group that fundamentally has distinct cultural feature that can be traced to each other’s natural state. The philosophical reflection in this article provides contemplative outlook on what is an ideology and how it materializes into some form of productivity embedded in every life of individual in the state